An Improved DSR Routing Algorithm to Reduce Delay and Energy Consumption in Mobile Ad Hoc Networks - Revathi, P; Gokul Raj, K (International Journal of Computer Sciences and Engineering, 2021)
Mobile Ad hoc Network (MANET) is a self-configuring, dynamic, multi-hop and infrastructure less wireless network. Each node in MANET is free to move arbitrarily in any direction. A node can move randomly and may join or leave in network at any time. Each node acts as host and intermediate nodes act as routers by using multi-hop schemes. The adhoc protocols are divided into proactive, hybrid and reactive protocols. In this paper, the Dynamic Source Routing (DSR) protocol is studied. This study focuses on how to reduce the delay while transferring the data using optimized DSR routing protocol. This mechanism is used to reduce the packet loss and time delay and to reduce energy consumption in MANET. This optimizing mechanism helps to choose the best and the shortest path to transfer the data. This mechanism controls routing overhead in MANET.